1999
DOI: 10.1074/jbc.274.22.15901
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nuclear Receptor Corepressor as a Peroxisome Proliferator-activated Receptor α Interacting Protein

Abstract: Nuclear receptor corepressor (NCoR) was demonstrated to interact strongly with peroxisome proliferator-activated receptor ␣ (PPAR␣), and PPAR␣ ligands suppressed this interaction. In contrast to the interaction of PPAR␣ with the coactivator protein, p300, association of the receptor with NCoR did not require any part of the PPAR␣ ligand binding domain. NCoR was found to suppress PPAR␣-dependent transcriptional activation in the context of a PPAR␣⅐retinoid X receptor ␣ (RXR␣) heterodimeric complex bound to a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 56 publications
7
81
0
2
Order By: Relevance
“…Indeed, supershift analysis revealed that SMRT only associates with DNA-bound PPAR␦ and not with DNA-bound PPAR␣ or PPAR␥ (data not shown). This is consistent with previous observations that neither PPAR␣ nor PPAR␥ was associated with corepressors when bound to DNA (23,36) and provides a basis for the unique repression property of PPAR␦. Because all three PPARs bind to common DNA sequences, the isoform-specific repression by PPAR␦ is likely because of recruitment of corepressors to PPRE.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Indeed, supershift analysis revealed that SMRT only associates with DNA-bound PPAR␦ and not with DNA-bound PPAR␣ or PPAR␥ (data not shown). This is consistent with previous observations that neither PPAR␣ nor PPAR␥ was associated with corepressors when bound to DNA (23,36) and provides a basis for the unique repression property of PPAR␦. Because all three PPARs bind to common DNA sequences, the isoform-specific repression by PPAR␦ is likely because of recruitment of corepressors to PPRE.…”
Section: Discussionsupporting
confidence: 81%
“…Although all three PPARs bind to nuclear receptor corepressors in solution (23,35,36), only PPAR␦ functions as a repressor in both GAL4 system and PPRE-mediated transcription. Possibly, PPAR␦ is the only PPAR isoform that associates with corepressors when bound to DNA.…”
Section: Discussionmentioning
confidence: 99%
“…One protein that has been found to associate with PPAR␣ is heat shock protein 72; however, the functional significance of this association has not been determined yet (21). The only other proteins reported to associate with PPAR␣ are co-activators such as PPAR␣-binding protein (designated PBP) (22), the steroid receptor co-activator 1 (23), p300 (24), peroxisome proliferator-activated receptor interacting protein (designated PRIP) (25), and nuclear receptor co-repressor (26). Thus, little is known about the regulation of PPAR␣ through protein-protein interactions.…”
mentioning
confidence: 99%
“…CARHSP1 binds to the 167-244 aa sequence of PPAR␣ which is located in the PPAR␣ hinge domain. Both the coactivator, PGC-1␣, and the corepressor, N-CoR, can also bind to this particular PPAR␣ domain (17,47). Notably, CARHSP1 down-regulation of gluconeogenic genes is dependent on PPAR␣.…”
Section: Discussionmentioning
confidence: 99%